Manajemen Kepala Sekolah Untuk Meningkatkan Mutu Pendidikan Pada Sekolah Penggerak SMA Assa’adah Bungah Gresik - Putri Zahrotul Ilmiyah; Ashari Ashari (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2023)
This study aims to determine the components that must be fulfilled by the principal of the driving school, the work program of the driving school principal and the success of the management of the principal in improving the quality of education. The research used is qualitative research with a case study approach, the data collection technique uses observation, interviews, and documentation. The data analysis technique uses data collection, data reduction, drawing conclusions. Meanwhile, to test the validity of the data using source triangulation. The results of the study show 1) Components that must be fulfilled by school principals to improve the quality of education must have five intelligences, namely: professional, personal, interpersonal intelligence, intelligence to carry out an independent curriculum, fulfillment of driving school requirements according to the Ministry of Education and Culture and Research and Technology number 371 of 2021, having a head activator certificate and attended training from the Ministry of Education and Culture. 2) School principal management to improve quality, namely by implementing work programs in the fields of curriculum, student affairs, public relations and sarpras, 3) The form of the success of the driving school principal's work program is that students succeed in making scientific work, forming a Pancasila student profile, students are able to become a team reliable broadcast and journalist, won the national level mathematics Olympiad, made banana chip products, provided quotas for graduates to continue on to tertiary institutions and work quotas at PT Atiga Langgeng Mandiri Gresik, SMA Assa'adah Bungah Gresik became facilitators of driving schools so as to create relationships Gresik high school synergy.